2022
DOI: 10.3390/molecules27217637
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Polyphenols as Prospective Natural-Compound Depression Treatment from the Perspective of Intestinal Microbiota Regulation

Abstract: The broad beneficial effects of dietary polyphenols on human health have been confirmed. Current studies have shown that dietary polyphenols are important for maintaining the homeostasis of the intestinal microenvironment. Moreover, the corresponding metabolites of dietary polyphenols can effectively regulate intestinal micro-ecology and promote human health. Although the pathogenesis of depression has not been fully studied, it has been demonstrated that dysfunction of the microbiota-gut-brain axis may be its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 129 publications
(128 reference statements)
0
5
0
Order By: Relevance
“…Ellagic acid has antioxidant, anti-inflammatory, and neuroprotective properties ( Ríos et al, 2022 ). Several recent reviews have discussed the antidepressant effects of compounds, such as amentoflavone, apigenin, chlorogenic acid, curcumin, and ferulic acid ( Pathak et al, 2013 ; Wang et al, 2022 ; Winiarska-Mieczan et al, 2023 ). In another study, Nigella sativa oil produced a positive motor coordinative effect on phenol-mediated essential tremors in a mouse model ( Folarin et al, 2020 ).…”
Section: Phenols and Neuropsychiatric Disordersmentioning
confidence: 99%
“…Ellagic acid has antioxidant, anti-inflammatory, and neuroprotective properties ( Ríos et al, 2022 ). Several recent reviews have discussed the antidepressant effects of compounds, such as amentoflavone, apigenin, chlorogenic acid, curcumin, and ferulic acid ( Pathak et al, 2013 ; Wang et al, 2022 ; Winiarska-Mieczan et al, 2023 ). In another study, Nigella sativa oil produced a positive motor coordinative effect on phenol-mediated essential tremors in a mouse model ( Folarin et al, 2020 ).…”
Section: Phenols and Neuropsychiatric Disordersmentioning
confidence: 99%
“…A part of ingested polyphenols is known to be degraded by intestinal bacteria in the colon. Several comprehensive reviews of these have been reported so far [20,150,151]. However, the amount and type of metabolic degradation of polyphenols by gut bacteria relative to the total polyphenols consumed, and the kinetics of this degradation, is not well understood.…”
Section: Bioavailability Of Polyphenolsmentioning
confidence: 99%
“…Moreover, various inflammatory molecules originating from the gut microflora (lipopolysaccharides, endotoxins, etc.) may activate the peripheral immune system, reach the brain, activate microglia, and promote the development of depression through cytokine release [ 284 , 286 , 287 ]. The microbiota–inflammasome hypothesis of major depressive disorder states that the dysbiosis of the gut microbiota deteriorates the integrity of the blood–brain barrier through peripheral inflammation.…”
Section: Flavonols and Gut–brain Axismentioning
confidence: 99%
“…On the other hand, polyphenols, including flavonols, need to be metabolized and activated by microorganisms in the gut. Via microbial metabolism, dietary polyphenols are broken down into small aromatic metabolites, some of which may directly act as neurotransmitters [ 287 , 293 ]. In fact, interactions between the microbiota and polyphenols in the diet are important factors in determining the effects of polyphenols on brain functions and the biological hallmarks of depression.…”
Section: Flavonols and Gut–brain Axismentioning
confidence: 99%
See 1 more Smart Citation